MARKETING INSTITUTIONS IN THE AGRIBUSINESS VALUE CHAIN: A LITERATURE REVIEW ON THE ROLES OF COOPERATIVES, COLLECTING TRADERS, AND TRADING COMPANIES - Ayyumi Khusnul Khotimah; Ayu Nursari; Lestari Wuryanti (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
Marketing institutions play a crucial role in shaping the performance and inclusiveness of agribusiness value chains, particularly in connecting producers to markets. This study aims to review the literature on the roles of marketing institutions, namely cooperatives, collecting traders, and trading companies within the agribusiness value chain. A qualitative approach was employed, utilizing a literature review design that drew on peer-reviewed articles indexed in Scopus and other reputable academic sources. The selected studies were analyzed thematically to identify key patterns related to institutional functions, market coordination, and value distribution. The findings indicate that cooperatives strengthen farmers’ bargaining power through collective action and market coordination. Collecting traders reduce transaction costs and facilitate market access in rural areas, while trading companies enable integration into regional and global markets through logistics management and quality standardization. These institutions perform complementary functions rather than substitutive roles within the agribusiness value chain. However, the effectiveness of marketing institutions is highly dependent on the quality of governance, organizational capacity, and the policy environment. Weak institutional arrangements and imbalanced power relations may lead to unequal value distribution and limited market inclusion for smallholders. This study contributes to the agribusiness literature by offering an integrative institutional perspective on marketing functions within value chains. The findings provide policymakers and practitioners with valuable insights for designing strategies that strengthen marketing institutions and promote more efficient, inclusive, and sustainable agribusiness value chains